2007
DOI: 10.1109/fie.2007.4417918
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of pre-engineering curricula on middle School Students’ attitudes to and knowledge of engineering careers

Abstract: The Middle School Students' Attitude to Mathematics, Science and Engineering Survey was developed to measure students' attitudes to engineering and knowledge about engineering careers as part of a program to enlarge the future pool of engineers because students' attitudes have been found to be an important predictor of whether students pursue careers in engineering. The program focuses on using pre-engineering curricula in middle and high schools, and informing students, teachers, parents, and school counselor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 8 publications
2
26
0
Order By: Relevance
“…Researchers calculated a Cronbach's alpha (0.86) to determine the internal consistency for the AMSE instrument; this value was consistent with the value reported (0.85) by Hirsch et al (2007). Table 2 presents the descriptive statistics and Wilcoxon Signed Rank test results for the seven AMSE subscales.…”
Section: Attitudes To Mathematics Science and Engineeringsupporting
confidence: 65%
See 4 more Smart Citations
“…Researchers calculated a Cronbach's alpha (0.86) to determine the internal consistency for the AMSE instrument; this value was consistent with the value reported (0.85) by Hirsch et al (2007). Table 2 presents the descriptive statistics and Wilcoxon Signed Rank test results for the seven AMSE subscales.…”
Section: Attitudes To Mathematics Science and Engineeringsupporting
confidence: 65%
“…Engineering and/or technology focused camps have been found to have positive impacts on students' views of engineering (Elam, Donham, & Soloman, 2012;Nadelson and Callahan, 2011) and technology (Nugent, Barker, Grandgenett, & Adamchuk, 2010). Additionally, outreach programs that incorporate engineering into the school curriculum have had positive impacts on students' views of engineering (Hirsch, Carpinelli, Kimmel, Rockland, & Bloom, 2007;Plant, Baylor, Doerr, & Rosenberg-Kima, 2009). Plant et al (2009) investigated the impact of using computer animated interface agents on 106 middle schools students' math performance and attitudes towards the utility of math and hard sciences and found that interacting with a female agent resulted in fewer gender-related perceptions of engineering in male students, but female students' perceptions remained unchanged.…”
Section: Programs To Improve Attitudes Toward Stemmentioning
confidence: 99%
See 3 more Smart Citations